2021
DOI: 10.2217/fon-2021-0121
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and COVID-19: Analysis of Patient Outcomes

Abstract: Background: We sought to investigate the outcomes associated with COVID-19 disease in cancer patients. Methods: We conducted a retrospective cohort study of laboratory-confirmed COVID-19 patients. Results: Of the 206 patients included, 57 had at least one preexisting malignancy. Cancer patients were older than noncancer patients. Of the 185 discharged cases, cancer patients had a significantly higher frequency of unplanned reintubation (7.1% vs 0.9%, p < 0.049), and required longer hospital stay (8.58 ± 6.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 22 publications
2
19
0
1
Order By: Relevance
“…In our cohort, our mean LOS of 11.2 days was likely affected by outlier cases (maximum LOS = 87 days). The median LOS for our hospitalized patients was 6 days and these findings were similar to other studies looking at hospitalizations for this patient population [15,16]. The average LOS for our hospitalized patients without COVID-19 during the same time period was 7.6 days.…”
Section: Discussionsupporting
confidence: 89%
“…In our cohort, our mean LOS of 11.2 days was likely affected by outlier cases (maximum LOS = 87 days). The median LOS for our hospitalized patients was 6 days and these findings were similar to other studies looking at hospitalizations for this patient population [15,16]. The average LOS for our hospitalized patients without COVID-19 during the same time period was 7.6 days.…”
Section: Discussionsupporting
confidence: 89%
“…It is also shown that mortality in the hospital setting for COVID-19-infected cancer patients is five times greater than the mortality of COVID-19 non-elderly and predisposing-condition-free patients [ 96 , 99 ]. However, in a retrospective cohort [ 100 ], the adverse outcomes were mainly attributed to the comorbidities that cancer patients present with, such as obesity, active smoking and old age. Moreover, although preliminary findings did not manage to support a significant association between recent cytotoxic chemotherapy treatment and adverse COVID-19 outcomes [ 101 ], later studies using larger cohorts demonstrated that cancer patients receiving chemotherapy or chemoradiotherapy had also an increased risk of worse outcomes, especially when the anticancer treatment had been administrated shortly before infection [ 98 ].…”
Section: Covid-19 and Cancermentioning
confidence: 99%
“…We identified three studies in the literature that compared the differences in characteristics and outcomes among 5542 COVID-19 infected patients with ( n = 398) and without malignancies ( n = 5144) [ 19 , 20 , 21 ]. Their outcomes are summarized in Table 1 .…”
Section: Covid-19 and Malignancymentioning
confidence: 99%
“…Additionally, patients who received surgery and immunotherapy presented with elevated mortality and increased incidence of severe symptoms, while this was not observed for those under radiotherapy [ 19 ]. Finally, Aboueshia et al detected no difference in mortality rates among patients with cancer who were currently under treatment (active) and those who were not (non-active) [ 21 ].…”
Section: Covid-19 and Malignancymentioning
confidence: 99%